2010
DOI: 10.1111/j.0960-7412.2010.04208.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of grapevine microRNAs and their targets using high throughput sequencing and degradome analysis

Abstract: In plants, microRNAs (miRNAs) comprise one of three classes of small RNAs regulating gene expression at the post-transcriptional level. Many plant miRNAs are conserved, and play a role in development, abiotic stress responses or pathogen responses. However, some miRNAs have only been found in certain species. Here, we use deep-sequencing, computational and molecular methods to identify, profile, and describe conserved and non-conserved miRNAs in four grapevine (Vitis vinifera) tissues. A total of 24 conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
274
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(326 citation statements)
references
References 61 publications
49
274
3
Order By: Relevance
“…In addition, unlike conserved miRNAs that often targeted multiple members of a gene family, most novel miRNAs targeted genes from different gene families. Similar observations were made in other plant species, reflecting the properties of young miRNAs (Pantaleo et al, 2010;Xia et al, 2012;Zhu et al, 2012).…”
Section: Two Clusters Of Novel Fve-mirnas Targeting Fbx Genessupporting
confidence: 86%
“…In addition, unlike conserved miRNAs that often targeted multiple members of a gene family, most novel miRNAs targeted genes from different gene families. Similar observations were made in other plant species, reflecting the properties of young miRNAs (Pantaleo et al, 2010;Xia et al, 2012;Zhu et al, 2012).…”
Section: Two Clusters Of Novel Fve-mirnas Targeting Fbx Genessupporting
confidence: 86%
“…The tissue-dependent variation in the pools of 24 and 21-nt classes has also been observed in other plant species (Pantaleo et al 2010) and, in a few cases, striking variation has been detected (Slotkin et al 2009) reflecting the sRNA biogenesis pathways operating in such tissues. The determined level of non-redundancy further showed that in both cork oak tissue types the 21-nt class is less diverse than the 24-nt class, which is in agreement with previous reports in other species Martínez et al 2011;Pantaleo et al 2010;Rajagopalan et al 2006). …”
Section: Discussionmentioning
confidence: 61%
“…In fact, previous reports refer that the 24-nt sRNAs is the predominant size class, for instance in Arabidopsis thaliana, Nicothiana benthamiana, Solano lycopersicum, Oriza sativa and Olea europea (Morin et al 2008;Pantaleo et al 2010;Donaire et al 2011;Kasschau et al 2007), while the 21-nt class is more abundant in species such as Eschscholzia californica, Hordeum vulgare, Vitis vinifera, Pinus contorta and Panax gynseng (Pantaleo et al 2010;Morin et al 2008;Schreiber et al 2011;Barakat et al 2007). The tissue-dependent variation in the pools of 24 and 21-nt classes has also been observed in other plant species (Pantaleo et al 2010) and, in a few cases, striking variation has been detected (Slotkin et al 2009) reflecting the sRNA biogenesis pathways operating in such tissues. The determined level of non-redundancy further showed that in both cork oak tissue types the 21-nt class is less diverse than the 24-nt class, which is in agreement with previous reports in other species Martínez et al 2011;Pantaleo et al 2010;Rajagopalan et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…GSM465746) and from a grapevine tree cultivar Pinot noir ENTAV115 (accession no. GSE18405) was downloaded from the Gene Expression Omnibus database of the NCBI (23,40). The reference sequences of PLMVd (accession no.…”
Section: Methodsmentioning
confidence: 99%